ALTERNATIF PENYELESAIAN SENGKETA PERDATA DIPENGADILAN - Jaidun Jaidun; Syaharie Jaang (Yuriska: Jurnal Ilmiah Hukum, 2024)
Settlement of civil disputes through a judge mediator is regulated in Article 1 paragraph (2) of the Republic of Indonesia Supreme Court Regulation number 1 of 2016 concerning Procedures for Mediation in Court which states that a mediator is a Judge or other party who has a Mediator Certificate as a neutral party to assist the Parties in the negotiation process to seek various possibilities for resolving disputes without having to make a decision or force a resolution. The parties can use Alternative Dispute Resolution to reach a mutually beneficial agreement. The research used is non-doctrinal legal research, or can also be called research about law. The data used is primary data, namely data obtained directly from research subjects such as interviews. Apart from that, secondary data comes from statutory regulations and literature. Then the data obtained was analyzed qualitatively. The parties use the services of a certified mediator, because this is influenced by 2 factors, namely: (1) They do not want to pay the costs of hiring a certified mediator (2) There are no provisions governing the obligations of the parties to use a certified mediator. The failure of the peace agreement between the parties was caused by 2 factors, namely: (1) Having a strong desire to take the litigation route. (2) It is difficult to entrust the resolution of legal conflicts to a mediator. (3) Still holding a grudge that is difficult to reconcile. Mediators provide convenience and open access to information for the parties to achieve peace. Obstacles to peaceful efforts in court are (1) The parties have a strong desire to resolve civil conflicts through litigation (court). (2) The parties find it difficult to trust the mediator to resolve their conflict. (3) Both parties still hold grudges that are difficult to reconcile